Risk of pulmonary embolism and deep vein thrombosis following COVID‐19: a nationwide cohort study - Hye Jun Kim; Seogsong Jeong; Jihun Song; Sun Jae Park; Young Jun Park; Yun Hwan Oh; Jaehun Jung; Sang Min Park (MedComm, 2024)
Abstract Recent studies elucidate that coronavirus disease 2019 (COVID‐19) patients may face a higher risk of cardiovascular complications. This study aimed to evaluate association of COVID‐19 with the risk of pulmonary embolism (PE) or deep vein thrombosis (DVT). This nationwide population‐based retrospective cohort study included Korean adult citizens between January 2021 and March 2022 from the Korea Disease Control and Prevention Agency COVID‐19 National Health Insurance Service cohort. The Fine and Gray's regression with all‐cause death as a competing event was adopted to evaluate PE and DVT risks after COVID‐19. This study included a total of 1,601,835 COVID‐19 patients and 14,011,285 matched individuals without COVID‐19. The risk of PE (adjusted hazard ratio [aHR], 6.25; 95% confidence interval [CI], 3.67–10.66; p < 0.001) and DVT (aHR, 3.05; 95% CI, 1.75–5.29; p < 0.001) was higher in COVID‐19 group in individuals without complete COVID‐19 vaccination. In addition, individuals with complete COVID‐19 vaccination still had a higher risk of COVID‐19‐related PE (aHR, 1.48; 95% CI, 1.15–1.88; p < 0.001). However, COVID‐19 was not a significant risk factor for DVT among those with complete COVID‐19 vaccination. COVID‐19 was identified as an independent factor that elevated PE and DVT risks, especially for individuals without complete COVID‐19 vaccination.